HOME DENTAL CARE: THE EXPANSION OF PRIMARY CARE (International Seven Journal of Health Research, 2025)
Home visits are an essential instrument of the Family Health Strategy (FHS), allowing direct interaction between health professionals and patients in their family environment. This article aims to report the performance of the Oral Health Team (OHT) of the João Mota Basic Health Unit (BHU), located in the urban area of Caruaru-PE, in home visits carried out in the second half of 2024, aimed at bedridden and domiciled patients. During these visits, the team performed basic dental procedures such as tooth extractions, supragingival scaling, and topical fluoride application. In addition to clinical actions, the OHT played an educational role, guiding caregivers on correct oral hygiene, including brushing technique and periodic toothbrush changes. The request for this demand came from the Community Health Agents, who identified the difficulty of this population in accessing the UBS due to reduced mobility. After the visits, an improvement in oral health conditions was observed and, consequently, in the quality of life of the patients, especially in terms of diet. The performance of the OHT in home visits demonstrates the application of the principle of equity in health, providing quality dental care to individuals in vulnerable situations. The team's intervention is essential to ensure access to oral health, improving quality of life and ensuring health rights for all patients.